Preparation, Physicochemical Properties and Intestinal Flora Regulatory Activity of Aqueous Extracts from Differently Pretreated Naematelia aurantialba - LIU Xiaoyu, LIU Liping, LIU Yanfang, FENG Jie, YANG Linlei, CAO Yao, ZHANG Jingsong, KANG Ji (Shipin Kexue, 2025)
Aqueous extracts (named NAP, NAPS and NAPH, respectively) from Naematelia aurantialba fruiting bodies subjected to three different pretreatments, namely, conventional grinding, steam explosion (SE) and high-pressure homogenization (HPH) were obtained by hot water extraction, and their yields, polysaccharide, uronic acid and protein contents, molecular mass distributions and monosaccharide compositions were compared. A simulated in vitro fermentation model was employed to investigate the effects of these extracts on the intestinal flora using high-throughput 16S rRNA gene sequencing. The results showed that the yields and polysaccharide contents of NAPS (64.15% and 75.87%, respectively) and NAPH (61.64% and 72.56%, respectively) were evidently higher than those of NAP. The molecular mass (mw) of NAP was 1.731 × 106 g/mol, which was higher than that of NAPH, and NAPS exhibited new characteristic peaks. NAP, NAPS and NAPH were all composed of mannose, xylose, glucose and glucuronic acid, and the monosaccharide composition changed slightly after SE and HPH. All extracts changed the composition of the intestinal flora. Both NAPS and NAP had an advantage in increasing the abundance of Macroomonas, NAPH increased the abundance of Bifidobacterium and Lactobacillus (P < 0.05), and NAP increased the abundance of Butyricicoccus (P < 0.05). The yields of short-chain fatty acids (SCFAs) significantly increased with the addition of each extract. Notably, butyric acid content was higher in the F-NAP group, while acetic acid and propionic acid contents were higher in the F-NAPH and F-NAPS groups. This study provides a reference for the efficient preparation of aqueous extracts from N. aurantialba and its application for regulating the intestinal flora.